Ashita no Joe. Fighting for tomorrow. 2 - Takamori, Asao, 1936-1987 (Kodansha USA Publishing, LLC, 2024)
After a stunning clash between Rikiishi's finely honed skill and Joe's raw, unbridled gift, both are released from Toko Reformatory--but Joe has a lot of catching up to do. His rival is already making waves on the pro circuit, and while Rikiishi has expensive, state-of-the-art training facilities, Joe has nothing but a makeshift gym down by the river. Danpei inspires him to dream of walking back across the so-called bridge of tears and into the limelight, but when the old pug's reputation catches up with him, it looks like Joe might be shut out of the pros forever...